Pengaruh Authoritative Parenting Style Terhadap Prestasi Belajar Anak SMA 7 Wajo - Andi Umra Syamra; Eva Meizara Puspita; Andi Nasrawaty Hamid (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
The achievement of children's learning achievement cannot be separated from the role and involvement of parents in nurturing and educating children. This study aims to determine the effect on the Authoritative Parenting Style of children's learning achievement. Subjects in this study found 301 students of SMAN 7 Wajo.This study uses quantitative methods and the hypothesis test used in this study is the ordinal regression analysis technique. The results of this study indicate that there is no significant effect between authoritative parenting style and student achievement at SMAN 7 Wajo (p=0.068). This shows that there is no influence between authoritative parenting on learning achievement. This research can be used as reference material and information about improving children's learning achievement based on parenting applied by parents